1975
DOI: 10.1037/0021-843x.84.4.366
|View full text |Cite
|
Sign up to set email alerts
|

Social modeling influences on psychophysical judgments of electrical stimulation.

Abstract: We examined the psychophysical power functions describing the relation between subjective judgments and electric shock intensity in 30 subjects exposed to social modeling influence procedures. Models simulated different levels of discomfort and pain susceptibility, ostensibly in response to the same shocks the subjects were receiving. Subjects observing a tolerant model accepted substantially greater shocks and on several measures reported no greater discomfort than those exposed to an intolerant model. A cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
3
18
0
Order By: Relevance
“…In support of this hypothesis is the recent report that laboratory mice have heightened pain behavior when exposed to cagemates, but not to strangers, in pain (Langford et al, 2006). Several human studies also showed that the exposure to an actor in pain (Craig and Weiss, 1971;Craig et al, 1975), or even the simple observation of pictures of human pain (Godinho et al, 2006) is associated with higher pain reports. However, by having changed the content of pain cues across conditions, none of these studies has separated the effects of empathy from those of other factors such as social modeling (Craig and Weiss, 1971;Craig et al, 1975), conditioned affective responses and/or mood alterations (Villemure et al, 2003;Rainville et al, 2005).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…In support of this hypothesis is the recent report that laboratory mice have heightened pain behavior when exposed to cagemates, but not to strangers, in pain (Langford et al, 2006). Several human studies also showed that the exposure to an actor in pain (Craig and Weiss, 1971;Craig et al, 1975), or even the simple observation of pictures of human pain (Godinho et al, 2006) is associated with higher pain reports. However, by having changed the content of pain cues across conditions, none of these studies has separated the effects of empathy from those of other factors such as social modeling (Craig and Weiss, 1971;Craig et al, 1975), conditioned affective responses and/or mood alterations (Villemure et al, 2003;Rainville et al, 2005).…”
Section: Introductionsupporting
confidence: 60%
“…Although several studies have shown that empathy activates pain-relevant cortical areas (see de Vignemont and Singer, 2006), and others have documented the effects of the observation of pain scenes on pain perception (Craig and Weiss, 1971;Craig et al, 1975;Godinho et al, 2006), remarkably, no study has yet shown that empathy itself increases pain sensitivity in humans. In a number of previous studies, subjects' pain sensitivity was reported to be higher during the observation of pain scenes (e.g., the pain behaviors of an actor, or pictures depicting burns, wounds) than during the observation of other scenes, in which there was less or no pain.…”
Section: Previous Studies On the Effects Of Pain Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the suggestion that TPEPs may grow more rapidly in observers with a small dynamic range deserves further investigation, particularly under conditions in which the stimulus set is predicated upon the tolerance as well as the sensation threshold. Craig et al (1975) showed that psychophysical exponents can be manipulated by social modeling influences (exposure of observers to tolerant models increases their pain tolerance and reduces the magnitude of their exponent). The dynamic range, the power function, and the cerebral evoked response may be tempered by an interaction of sensory, motivational, and cognitive processes, and not by sensory factors alone.…”
Section: Corresponding Analysis Of Evoked Potential Datamentioning
confidence: 99%
“…Although there This research was supported by Grant AO-392 from the Natural Sciences and Engineering Research Council of Canada to the senior author. Requests for reprints should be sent to Gary B. Rollman, Department of Psychology, University of Western Ontario, London, Ontario N6A 5C2, Canada. have been attempts to obtain psychophysical functions for intense stimuli in several modalities (e.g., Adair, Stevens, & Marks, 1968;Cooper, Vierck, & Yeomans, 1986;Craig, Best, & Ward, 1975;Ekmanet al, 1964;Gracely, McGrath, & Dubner, 1978;Grossberg & Grant, 1978;Hilgard et al, 1974;Hill, Flanary, Kernetsky, & Wikler, 1952;Starn, Petrusic, & Spanos, 1981;Sternbach & Tursky, 1964;Tursky, Jamner, & Friedman, 1982), at present considerably more is known about the psychophysics of thermal pain than about electrocutaneous discomfort.…”
mentioning
confidence: 99%